2016
DOI: 10.18632/oncotarget.9261
|View full text |Cite
|
Sign up to set email alerts
|

Functional cooperation between KCa3.1 and TRPC1 channels in human breast cancer: Role in cell proliferation and patient prognosis

Abstract: Intracellular Ca2+ levels are important regulators of cell cycle and proliferation. We, and others, have previously reported the role of KCa3.1 (KCNN4) channels in regulating the membrane potential and the Ca2+ entry in association with cell proliferation. However, the relevance of KC3.1 channels in cancer prognosis as well as the molecular mechanism of Ca2+ entry triggered by their activation remain undetermined. Here, we show that RNAi-mediated knockdown of KCa3.1 and/or TRPC1 leads to a significant decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 63 publications
(76 reference statements)
3
73
1
Order By: Relevance
“…KCa3.1 expression is often functionally linked to abnormal cell behaviors in multiple tumors, such as proliferation, apoptosis, and migration . Our results demonstrated that knockdown of KCa3.1 suppressed the proliferation, migration, invasion, and induced cell cycle arrest of HCC cells.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…KCa3.1 expression is often functionally linked to abnormal cell behaviors in multiple tumors, such as proliferation, apoptosis, and migration . Our results demonstrated that knockdown of KCa3.1 suppressed the proliferation, migration, invasion, and induced cell cycle arrest of HCC cells.…”
Section: Discussionmentioning
confidence: 59%
“…How could KCa3.1 expression influence the progression of tumors? Early reports have mainly focused on the intracellular calcium alterations induced by KCa3.1, which might explain the cellular biological behaviors resulting from KCa3.1 manipulation . Epigenetic dysregulation of KCa3.1 occurs in lung cancer and is associated with a worse prognosis of lung cancer patients .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the K ϩ channel types whose overexpression has been most implicated in proliferation of various cancer cells are voltage-gated K v 10.1 (EAG1, human gene KCNH1) (374) and K v 11.1 (HERG1, human gene KCNH2) (16,241,282), background K 2P 2.1 (TREK1, human gene KCNK2), K 2P 9.1 (TASK3, gene KCNK9) and K 2P 10.1 (TREK2, gene KCNK10) (386,398,512,534,561), Ca 2ϩ -dependent K Ca 1.1 (BK, Slo or MaxiK, gene KCNMA1) (42,162,347,363), and K Ca 3.1 (IK, gene KCNN4) (142,274), although the involvement of some other members from these groups was documented as well (reviewed in Refs. 226,385,496)…”
Section: Deregulation Of Cellular Electrogenesis In Cancermentioning
confidence: 99%
“…It was reported in previous studies that specific lncRNAs might be potent prognostic and predictive biomarkers [28, 29]. LncRNAs do have some advantages as clinical biomarkers.…”
Section: Discussionmentioning
confidence: 99%